Duration of fever and other symptoms after the inhalation of laninamivir octanoate hydrate; comparison of the 2011/12 to 2015/16 Japanese influenza seasons. Issue 9 (September 2017) - Ikematsu, Hideyuki; Kawai, Naoki; Iwaki, Norio; Kashiwagi, Seizaburo
Abstract: The duration of fever and symptoms after laninamivir octanoate hydrate (laninamivir) inhalation were investigated in the Japanese 2015/16 influenza season, and the results were compared with those of the 2011/12 to 2014/15 seasons. A total of 1068 patients were evaluated for the duration of fever and symptoms in the five studied seasons. The influenza types/subtypes were 125 A(H1N1)pdm09 (62.2%), 17 A(H3N2) (8.5%), and 59 B (29.4%) in the 2015/16 season. The median durations of fever were 40.0, 41.0, and 47.0 h, and the median durations of symptoms were 87.0, 76.0, and 93.0 h for A(H1N1)pdm09, A(H3N2), and B, respectively, with no significant difference. The median durations of fever were 52.0 and 46.0 h and the median durations of symptoms 93.0 and 88.0 h for the Victoria and Yamagata B lineages, respectively, with no significant difference. Fever resolution after laninamivir inhalation by the A(H1N1)pdm09 patients was similar in the 2013/14 and 2015/16 seasons. Fever resolution after laninamivir inhalation was similar in all comparisons of the 2011/12 to 2015/16 seasons for both A(H3N2) and B, with no significant difference among the five seasons. Over the seasons tested, eight adverse drug reactions (ADRs) were reported for 1128 patients. The most frequent ADR was diarrhea, and all ADRs were resolved and not serious. These results indicate the continuing clinical effectiveness of laninamivir against influenza A(H1N1)pdm09, A(H3N2), and B, with no safety issues.